The labor market integration of immigrant women in Europe: context, theory and evidence - Bentley Schieckoff; Maximilian Sprengholz (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2021)
Women represent an important component of the immigration population in Europe and have increasingly been a group of interest in academic studies, especially with regard to their integration outcomes. In this overview, we seek to provide a comprehensive resource for scholars of female immigrant labor market integration in Europe, to act both as a reference and a roadmap for future studies in this domain. We begin by presenting a contextual history of immigration to and within Europe since the Second World War, before outlining the major theoretical assumptions about immigrant women's labor market disadvantage from economics and sociology. We then synthesize the empirical findings published between 2000 and 2020 and analyze how they line up with the theoretical predictions. We also present descriptive analyses with data from 2019, which expose any discrepancies between the current situation in European countries and the situation during the time periods considered in the reviewed studies. As a group, immigrant women are often reported to experience significant disadvantages in their labor market integration, both compared to immigrant men and to native women. However, this type of approach glosses over the substantial heterogeneity in immigrant women's experiences. Instead, our overview points to a selective disadvantage for immigrant women that is highly dependent on their country of origin and the reception context they encounter after immigration.
urn:nbn:de:bsz:352-2-14p6dm0d1nmpr3
Keywords: J0; J61; 300; Labor market disadvantage; gender gap; nativity gap